Scripting Reality in the Legal Workplace: Women Lawyers, Litigation Prevention Measures, and the Limits of Anti-Discriminatiion Law - Bisom-Rapp, Susan (Columbia Journal of Gender and Law, 1996)
During my third year of legal practice, a single spoken sentence led me to consider at length the position of women attorneys in Wall Street law firms. Commenting on my recent announcement that I was pregnant, a male partner assured me, “In this department you will be treated as an attorney, not as a pregnant woman.” I puzzled over this dichotomy, wondering about the choice the partner had imposed on himself. Although I was pregnant and an attorney, he preferred not to see me as a pregnant attorney. This required a linguistic move, a kind of figurative bifurcation, that would appear positively bizarre if executed in reference to my male counterparts. My professional status was severed from my sex and physical condition. The partner’s choice of words was undoubtedly influenced by the dichotomous analytic framework of employment discrimination law, the area in which he practices. The prototypical discrimination case, the so-called single motive case, assumes that there is one “true” reason for an adverse employment action such as a discharge or failure to promote: either a good legitimate reason or a bad, discriminatory one. While effective in rooting out blatantly discriminatory actions, this model cannot accommodate decisions resulting from a complex mix of reasons that defy disaggregation. Yet it is routinely employed in just this sort of case.